Konsep khalifah sebagai landasan kepemimpinan dalam pendidikan islam - Isnaini, Karina (Maliki Interdisciplinary Journal, 2025)
This article discusses the Islamic concept of khalifah as a philosophical and ethical foundation for leadership models in Islamic education. In the Society 5.0 era, educational leaders are required not only to master managerial and technological aspects but also to possess strong spiritual integrity and moral responsibility. The concept of khalifah places a leader as God's vicegerent on earth, entrusted to uphold justice, maintain balance, and create public benefit. This study employs a qualitative approach using library research, analyzed descriptively through content analysis. The findings indicate that implementing khalifah values in Islamic educational leadership can cultivate visionary, trustworthy, and just leaders who serve as moral and spiritual role models for students and the entire school community.